Effects of coal mining subsidence on soil anti-erodibility in the loess mining area of northern Shaanxi, middle reaches of the Yellow River - Li, Quan; Song, Shijie; Ma, Haizhen; Wu, Jiaming; Wu, Hanbin; Sun, Yanjie (Frontiers in Environmental Science, 2026)
BackgroundA scientific understanding of soil erosion in coal mining subsidence areas is crucial for promoting green development and ecological restoration within the large coal bases of the Yellow River’s middle reaches.MethodsThis study focused on the shallow soil layer (0–40 cm) of a loess mining subsidence area and typical slopes in northern Shaanxi. Integrating field sampling, laboratory measurements, and model-based calculations, we analyzed the impact of mining subsidence on soil anti-erodibility by examining the coupled “slope position × soil depth” effect.ResultsThe results indicate that: (1) Mining subsidence significantly reduced the content of water-stable aggregates (>0.25 mm) and decreased the mean weight diameter of soil aggregates on the loess slope, with the >0.25 mm aggregate content being the most affected; (2) The adverse effect of subsidence on key soil anti-erodibility indicators weakened progressively from the slope top to the slope toe. The 0–20 cm soil layer at the slope top showed the greatest sensitivity; (3) Following subsidence, the comprehensive soil anti-erodibility index decreased significantly, indicating markedly enhanced erosion susceptibility. The most pronounced reduction (97.13%) was observed in the “slope top + 0–20 cm soil layer”.ConclusionThe “slope top + 0–20 cm soil layer” should be prioritized as a key area for erosion control on subsided loess slopes. These findings provide a scientific basis for targeted soil erosion management in coal mining subsidence areas of northern Shaanxi.